A Review of Indian Women Employed in the Informal Economy (Journal of Advances and Scholarly Researches in Allied Education, 2024)
As the world economy undergoes dramatic changes, this review article takes a look at the difficulties encountered by women in India who work in the informal sector. Women, especially those seeking work outside of agriculture, have a lot of options in India's unorganised economy. Wage inequality, dangerous working conditions, and a lack of social safeguards are just a few of the many challenges that women in this industry face, despite their increasing involvement. This research examines the decline in women's labour force participation and identifies many causes, including agricultural mechanisation, low salaries, and rising family incomes. Furthermore, it delves into the unique challenges that women encounter, such as prejudice based on gender, inadequate education, and the prevalence of sexual harassment. This study highlights the importance of the informal sector to India's economy and the need for specific measures to enhance the working conditions and economic security of women in this sector.